Pore-scale numerical simulation of in situ microemulsion formation and enhanced oil recovery in porous media - Hu, Yingxue; Dong, Kai; Zhang, Dan; Wu, Tianjiang; Xu, Wei; Gu, Zhaolin (Frontiers in Chemistry, 2025)
In situ microemulsion has emerged as an advanced tertiary oil recovery technique that utilizes the injection of surfactant solutions to improve displacement efficiency through spontaneous microemulsification. This study presents a novel pore-scale numerical model to simulate the dynamic process of in situ microemulsion formation during surfactant-cosolvent-salt flooding in complex porous media. Through comprehensive numerical simulations based on realistic rock geometries, we systematically investigated the spatiotemporal evolution of phase distributions and identified critical mechanisms governing oil mobilization. The developed model incorporates four fundamental characteristics of microemulsion systems: interfacial tension reduction, viscosity modification, wettability alteration, and enhanced solubilization capacity. During the microemulsion-forming surfactant flooding in a realistic rock medium, the in situ formed microemulsion was observed at the interface between oil and aqueous. The in situ microemulsion flooding can significantly improve the recovery rate under the combined effect of multiple factors. Increasing the viscosity of the in situ formed microemulsion can enhance the oil recovery during the microemulsion-forming surfactant flooding in the complex porous media. Under water-wet conditions, the oil-water interface stays at the junction of the throat and the pore space, which contributes to the formation of microemulsions and thus to the enhancement of recovery. This study provides a better understanding of the in situ microemulsion formation and the mechanisms of enhanced oil recovery in complex porous media.